Model Asuhan Keperawatan Terhadap Peningkatan Adaptasi Kognisi dan Biologis pada Pasien Terinveksi HIV - Nursalam Nursalam (Jurnal Ners, 2011)
Introduction: PAKAR model that focused on coping strategy and social support (nurse, family and patients) lead to positive coping mechanism through the learning process. The purpose of the study was to examine the effect of PAKAR toward adaptive response on PWH infection. PNI and nursing sciences from Roy paradigm were used in this study. Method: Quasy-experimental pre-post-test non randomized control group design is used in this study. Forty (40) PWH infections in Intermediate Department Care for Infection Disease (UPIPI) Dr. Soetomo hospital in Surabaya were selected and non-randomized assignment divided into 2 groups of 20, experiment and control group. In vitro- test were used to measure biological response change: cortical, CD4, IFNγ, and Anti-HIV. Psychological, social, and spiritual response were measured and observed by using questionnaires, in depth interview and Focus Group Discussion. A Multivariate analysis was used to evaluate the data of biological response and non-parametric test: Wilcoxon and Mann Whitney were used to measure cognitive response. Result: Result showed that there were significantly differences on cognitive response between PAKAR and Standard, namely; spiritual response on be patient, social response on emotional stable, and acceptance response on anger and bargaining. In addition, biological response were significantly differences between the groups with F = 0.497 and p = 0.000. The cortical and Anti-HIV variables were the pattern contribution between the groups, with 77.5%. The increase the number of CD4 was found to be the dominance factor that was correlated toward the positive of cognitive response caused by PAKAR. Discussion: PAKAR model that focused on coping strategy and utilizing social support lead to treat cognitive response PWH infection. The model is based on nursing science theory (Roy and Hall) combined with psychoneuroimmunology paradigm that is able to induce immune response modulation, especially the increase of the number of CD4. The increase of CD4 will induce IFN-γ to help macrophage in destroying HIV.